2020
DOI: 10.1002/elan.202000007
|View full text |Cite
|
Sign up to set email alerts
|

Validated Voltammetric Method for the Simultaneous Determination of Anti‐diabetic Drugs, Linagliptin and Empagliflozin in Bulk, Pharmaceutical Dosage Forms and Biological Fluids

Abstract: A cobalt oxide nanoparticles (Co3O4NPs) and multi walled carbon nanotubes (MWCNTs) modified carbon paste electrodes were used to study the electrochemical behavior of linagliptin and empagliflozin in Britton Robinson buffer solution of pH 8.0 using cyclic and square wave voltammetry. The above mentioned modified electrodes showed highly sensitive sensing and gave an excellent anodic response for both drugs. The peak current varied linearly over the concentration ranges: 3.98×10−5–1.53×10−3 mol L−1 (18.82–723.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The extensive ability of the analytical technique to remain unaffected by minor variations in the conditions of the method such as pH (4.0 AE 0.1) as well as each measurement resting period (5 s AE 1 s) is known as robustness. 59 No remarkable variations were noted in the results, reecting the robustness and method's reliability Table 1.…”
Section: Methods Validationmentioning
confidence: 96%
“…The extensive ability of the analytical technique to remain unaffected by minor variations in the conditions of the method such as pH (4.0 AE 0.1) as well as each measurement resting period (5 s AE 1 s) is known as robustness. 59 No remarkable variations were noted in the results, reecting the robustness and method's reliability Table 1.…”
Section: Methods Validationmentioning
confidence: 96%
“…Literature review showed that limited methods of analysis were established for simultaneous determination of the triple combination such as HPLC [ 6 8 ], HPTLC[ 6 , 9 ], UPLC [ 10 ] and spectrophotometry [ 11 ],whereas, for their binary combinations, HPLC [ 12 14 ], HPTLC [ 15 – 17 ], UPLC [ 17 ], voltammetric method [ 18 ] and spectrophotometric methods were reported [ 19 – 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, they lack of being simple, fast, and cost-effective approaches due to the required costly complex instrumentation and time-consuming multipart analytical procedures. In addition, a voltammetry method has been reported for the analysis and bioanalysis of EFN in pharmaceutical dosage form and human urine [ 27 ]. Spectrophotometric and chemometric methods were reported for EFN by the first author [ 28 ], but those methods missed the known higher sensitivity output of the spectrofluorometric analysis.…”
Section: Introductionmentioning
confidence: 99%